UN development aid : criteria and methods of evaluation - Leonard, William R.; Jenny, Beat Alexander; Nwali, Offia; United Nations Institute for Training and Research (New York : Arno Press, 1971)
The is a United Nations Institute for Training and Research (UNITAR) study examining the criteria and methods of evaluating UN development aid. It comprise of two parts. The first discusses the principal problems involved in planning and management of development projects, stressing the critical importance of systems employment and utilization. The second part deals with the tools of analysis based on modern management techniques. The book is geared primarily for use by personnel from developing countries who have some post-secondary education but limited training in economics, and statistics.
At head of title: United Nations Institute for Training and Research.
"A UNITAR study."
Includes bibliographical references.
lje 10/5/18
Loans
Keywords: Economic assistance; Economic aid; Economic development